2014
DOI: 10.1111/jsap.12311
|View full text |Cite
|
Sign up to set email alerts
|

Faecal shedding of antimicrobial‐resistant Clostridium difficile strains by dogs

Abstract: Healthy dogs can shed antimicrobial-resistant C. difficile strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 35 publications
3
24
2
Order By: Relevance
“…Another well‐known human RT is RT010, which was recently also found in dogs (Álvarez‐Pérez et al . ; Rabold et al . ) and in rabbits (Drigo et al .…”
Section: Resultsmentioning
confidence: 99%
“…Another well‐known human RT is RT010, which was recently also found in dogs (Álvarez‐Pérez et al . ; Rabold et al . ) and in rabbits (Drigo et al .…”
Section: Resultsmentioning
confidence: 99%
“…The nontoxigenic ribotype 010 has been isolated from dogs in Spain (Álvarez‐Pérez et al . ). This ribotype has been also described in several animal species, especially companion animals, as well as in some human samples (Keel et al .…”
Section: Discussionmentioning
confidence: 97%
“…Four out of 12 MDR isolates were nontoxigenic, which agrees with a previous study that showed that nontoxigenic ribotypes were highly resistant to clindamycin and erythromycin (Álvarez‐Pérez et al . ), highlighting the importance of these and similar strains may have as a source for antimicrobial resistance traits to other bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different other studies have associated the presence of C. difficile in faeces with diarrhoea in dogs and cats (Weese et al 2001a;2001b;Weese and Armstrong 2003;Koene et al 2012;Wetterwik et al 2013). However, dogs can also be healthy carriers of C. difficile strains belonging to human epidemic PCR-ribotypes (Schneeberg et al 2012;Silva et al 2013b;Spigaglia et al 2015), with a high colonisation in the first period of live (Perrin et al 1993;Á lvarez-Pérez et al 2015).…”
mentioning
confidence: 99%